Cross-country evidence on the determinants of preferences for redistribution - Gianluca Grimalda; David Pipke (Kiel Institute for the World Economy (IfW), 2021)
Redistribution differs widely across countries, but our understanding of why this is the case is limited. In democracies, the extent of redistribution should ultimately reflect citizens' preferences. We measure preferences for redistribution in six developed countries through internationally standardized questions in which respondents are faced with realistic budgetary constraints on their choice. We also measure a broad array of demographic, attitudinal, and ideological characteristics and examine their correlations with the preferred pattern of redistribution. As expected, individual income is associated with lower demand for redistribution, but this relationship loses significance once other factors are controlled for. Beliefs on social mobility have, in the aggregate, the largest effect in reducing demand for redistribution, the effect being largest in the US but insignificant in Italy and Slovenia. Trust in government has a negative effect on demand for redistribution across all countries. In line with other studies, we interpret this result as evidence that people believing that the political élite is corrupt demand more redistribution. Financial security, a proxy for the Prospect of Upward Mobility hypothesis, is also a significant correlate of preferences for redistribution, the effect being largest in Japan but small in the UK and Slovenia. Finally, discrimination of racial minorities is associated with lower demand for redistribution, but the effect is only significant in the US and Germany. Overall, the main theories that have been proposed to account for preferences for redistribution are confirmed to be valid, but with significant variation across countries.
Keywords: 330; Umverteilung; Präferenztheorie; Befragung; Vergleich; Großbritannien; USA; Japan; Italien; Slowenien; Deutschland